Reconstruction of Shared Assets Due to Divorce Based on Pancasila Justice - Mustofa Aditama; Meysita Arum Nugroho (JURNAL HUKUM SEHASEN, 2022)
The implementation of the distribution of joint property due to divorce is currently not fair, meaning that the construction of the distribution of joint property due to divorce is currently given by the Marriage Law no. 1 of 1974, the Compilation of Islamic Law still does not fulfill the sense of justice. This study aims to determine, find and analyze how the reconstruction of the distribution of joint property due to divorce based on the value of Pancasila justice. The results of the study on the reconstruction of the legal value of the distribution of joint property due to divorce were carried out in a casuistic manner based on their contribution by taking into account the benefits and disadvantages. The reconstruction of the value of justice as a result of divorce based on the orientation of the distribution is solely for the benefit, benefit and benefit of the person concerned, on the contrary, certain situations and conditions that can harm the interests and welfare of one party must be avoided.